Double trouble Groundhog Day - Roberts, Bethany (Henry Holt and Co., 2008)
When Grampie Groundhog decides to retire from forecasting the weather, he has twins Greta and Gregory draw straws to see who will take over the important job, but the winner is so nervous the two put aside their squabbling and work together.